Damping rate of a massive fermion in a hot medium - Henning, P.A. (Condensed Matter Physics, 2000)
In a hot system every excitation acquires a ﬁnite lifetime, manifesting itself in a non-zero spectral width. Ordinary damping as well as quantum memory effects arise from this nontrivial spectral function. This report presents a new method for the self-consistent calculation of the spectral width of a fermion coupled to massless bosons of scalar, vector and pseudoscalar type. In accordance with the known procedures of Quantum Electrodynamics, the self-consistent summation of the corresponding Fock diagram eliminates all infrared divergences although the bosons are not screened at all. The solutions for the fermion damping rate are analytical in the coupling constant g , but not analytical in the temperature parameter, i.e., γ ∝ g²T + O(g⁴T log(T /M )) .